The relative contributions of traffic and non-traffic sources in ultrafine particle formations in Tehran mega city - Jafarigol Farzaneh; Yousefi Somayeh; Darvishi Omrani Ali; Rashidi Yousef; Buonanno Giorgio; Stabile Luca; Sabanov Sergei; Amouei Torkmahalleh Mehdi (Springer Science and Business Media LLC, 2024)
Emissions of ultrafine particles (UFPs; diameter 10 nm at nine stations and understand the major sources of UFP s (primary vs. secondary) in Tehran megacity. The study was carried out in Tehran in 2020. NOx and PNC were reported from a total of nine urban site locations in Tehran and BC concentrations were examined at two monitoring stations. Data from all stations showed diurnal changes with peak morning and evening rush hours. The hourly PNC was correlated with NOx. PNCs in Tehran were higher compared to those of many cities reported in the literature. The highest concentrations were at District 19 station (traffic) and the lowest was at Punak station (residential) such that the average PNC varied from 8.4 × 10 3 to 5.7 × 10 4 cm −3 . In Ray and Sharif stations, the average contributions of primary and secondary sources of PNC were 67 and 33%, respectively. Overall, we conclude that a decrease in primary emission leads to a decrease in the total concentration of aerosols, despite an increase in the formation of new particles by photo nucleation.